2016
DOI: 10.1007/s10862-016-9552-z
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Anxiety and Depressive Symptoms in Middle Childhood: the Role of Repetitive Thinking about Negative Affect and about Mother

Abstract: Two studies with two independent samples aimed to investigate whether repetitive thinking about negative affect (RTna) and repetitive thinking about mother (RTm) can be mechanisms in the association between attachment anxiety and depressive symptoms in middle childhood. In Study 1 (N = 381) and Study 2 (N = 157) 9-to 12-year-olds completed self-report questionnaires measuring attachment, RTna and depressive symptoms. In Study 2, additionally, a questionnaire was developed to measure RTm, and a compound score f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 90 publications
(130 reference statements)
0
21
0
1
Order By: Relevance
“…With regard to the RTm questionnaire, there is first promising support of the validity of this novel research instrument in two different samples (Van de Walle, Bijttebier, Braet, et al, 2016;Van de Walle et al, 2014). However, despite these interesting findings, the current study was conducted on the same sample as Van de Walle et al (in press).…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the RTm questionnaire, there is first promising support of the validity of this novel research instrument in two different samples (Van de Walle, Bijttebier, Braet, et al, 2016;Van de Walle et al, 2014). However, despite these interesting findings, the current study was conducted on the same sample as Van de Walle et al (in press).…”
Section: Limitationsmentioning
confidence: 99%
“…Convergent evidence shows that repetitive thinking is involved in the onset and maintenance of depressive symptoms (Ehring & Watkins, 2008;Watkins, 2008). Van de Walle, Bijttebier, De Raedt, et al (2014) and Van de Walle, Bijttebier, Braet, et al (2016) demonstrated that the link between less trust in maternal support and more depressive symptoms was partially mediated by more RTm during distress. More specifically, children with less trust indicated that, during distress, they had more frequent thoughts about the mother that they experienced as repetitive, intrusive, and difficult to disengage from, as capturing cognitive capacity, and as being unproductive.…”
Section: An Increased Attentional Focus On the Mother And The Breadthmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an accumulating number of studies showed that a narrower attentional field around mother serves as a protective factor for more securely attached children, but as a risk factor for more insecurely attached children. This effect was found for emotional and behavioral problems Van de Walle et al, 2016) and for non-suicidal self-injury (Claes et al, 2016). It has been proposed that having a narrower attentional field around the mother may be helpful during distress for more securely attached children because it can facilitate support seeking behavior.…”
Section: The Moderating Role Of Children's Attentional Breadth Aroundmentioning
confidence: 95%